Effect of cold treatment on germination of Saxifraga aizoides and S. paniculata: a comparison of central (eastern Alps) and southern populations (northern Apennines) - Landi Marco; Biondini Silvia; Zoccola Antonio; Gobbo Gino; Betti Adriano; Saveri Carlo; Terlicher Patrizio; Bottacci Alessandro; ANGIOLINI, CLAUDIA (Biologia, 2016)
The best duration of cold treatment for germination of Saxifraga aizoides and S. paniculata was investigated comparing seeds collected from Alpine and Apennine populations. For S. aizoides seeds of both provenances, the highest germination was obtained after 12 weeks of cold treatment, and Apennine seeds showed the best performance. For S. paniculata, the effect of cold treatment differed greatly in relation to provenance: Alpine seeds showed theirs highest germination after 20 weeks, while Apennine seeds showed their best, albeit low, germination percentage after 8-16 weeks. For both species, a maximum germination plateau was reached 20 days after sowing. Thus, for ex situ conservation and restoration projects in the Apennines, we suppose that S. aizoides seeds should be collected from the location closest to the restoration site and S. paniculata seeds from the Alps. These results also suggest that specific responses to cold treatment exist within the genus Saxifraga in relation to provenance.